2018
DOI: 10.1016/j.jmb.2018.04.034
|View full text |Cite
|
Sign up to set email alerts
|

p73 Alternative Splicing: Exploring a Biological Role for the C-Terminal Isoforms

Abstract: p73 (encoded by TP73 gene) is a p53 related protein that functions as a transcriptional factor. Similarly to p53, following DNA damage, p73 is stabilized and activated and controls expression of target genes that are involved in the regulation of cycle arrest and apoptosis. However, great complexity to the function of this gene is given by the wide range of its non-tumor-related roles, which include neurological development, ciliogenesis and fertility. From the structural point of view, p73 displays an intrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 50 publications
3
56
0
Order By: Relevance
“…As these isoforms lack either the TAD (ΔNp73 α ) or the SAM (TAp73 β ) (Fig. 1b ) 22 , they aid in defining the p73 domain responsible for binding to MCL1. We observed that both ΔNp73 α and TAp73 β Co-IP with the pulldown of MCL1 protein (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As these isoforms lack either the TAD (ΔNp73 α ) or the SAM (TAp73 β ) (Fig. 1b ) 22 , they aid in defining the p73 domain responsible for binding to MCL1. We observed that both ΔNp73 α and TAp73 β Co-IP with the pulldown of MCL1 protein (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, both the full length TAp73 and the truncated ΔNp73 isoforms can be alternatively spliced at their C-termini (ΔN/TAp73 α , β , δ , ε , ϕ , γ , η ), generating up to seven C-terminal isoforms per N-terminal variant. There are two additional alternatively spliced N-terminal isoforms, ΔEx2-p73 and ΔEx2/3-p73, generating up to 28 hypothetical p73 variants in total 19 , many of which are currently of unknown significance 22 . All of these p73 isoforms retain their DBD and the TD, suggesting that they all maintain the ability to bind DNA and associate with one another 19 , 22 .…”
Section: Introductionmentioning
confidence: 99%
“…p63 is a member of a multigene family that includes p53 and p73. The p63 and p73 were originally identified based on homology to the major functional domains of p53: transactivation (TA), DNA binding (DBD), and oligomerization; all members of this family can present as multiple protein isoforms . p63 exists as two subclasses, TA and ΔNp63, due to the use of alternate gene promoters .…”
Section: The P53/p63/p73 Family Of Transcription Factorsmentioning
confidence: 99%
“…The p63 and p73 were originally identified based on homology to the major functional domains of p53: transactivation (TA), DNA binding (DBD), and oligomerization 5,12 ; all members of this family can present as multiple protein isoforms. 5,[12][13][14][15] p63 exists as two subclasses, TA and ΔNp63, due to the use of alternate gene promoters. 5 Additional complexity results from c-terminal alternative splicing of transcripts of both the TA and ΔNp63 subclasses, yielding at least 10 distinct isoforms.…”
Section: The P53/p63/p73 Family Of Transcription Factorsmentioning
confidence: 99%
“…TAp73 is the longest isoform encoded by the p73 gene, a member of the p53 family of transcription factors [1][2][3], which plays important roles in tumor suppression [4][5][6][7][8] and cellular homeostasis by promoting the expression of genes to regulate metabolism [9][10][11][12][13][14][15][16][17]. The p53 family also includes p53 and p63 that share with p73 the capability of promoting cell cycle arrest and apoptosis following DNA damage [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%